Caracterização físico-química e estrutural de complexos amido-monoestearato de glicerol em amidos de cereais e a influência da β-ciclodextrina - Garcia, Marina Costa [UNESP] (2013)
Effect of β-cyclodextrin (βCD) in the formation of amylose-lipid and / or amylopectin-lipids complexes using glycerol monostearate (GMS) (1, 2, 3% w/w), and wheat, normal corn, waxy corn and high amylose starches were physicochemically and structurally evaluated in the presence or absence of β-cyclodextrin (βCD) (3% w/w). Normal corn and wheat starches were characterized by similar amylose content (~ 25%) and A-type X-ray pattern. High amylose corn starch (49.8%) presented the B-type crystalline pattern, whereas the waxy corn starch with A-type crystalline pattern had 1.1% of amylose. The higher lipid (0.75%) and phosphorus (0.05%) contents in wheat starch contributed to its lower gelatinization temperature. Addition of βCD in native starches suggested that this oligosaccharide interfered in the formation of amylose-lipid complexes naturally present in starches, more intensely in the wheat starch mainly due to their higher content and type of lipids. Addition of GMS reduced breakdown and setback in wheat, normal corn and waxy corn starches due to the retrogradation complications of the amylose and/or complexed amylopectin molecules. After the βCD addition, there was an increase of ΔHcx for wheat, normal corn, and high amylose corn starches, suggesting the amylose-GMS complex disruption by βCD and a possible association between βCD and GMS. The produced complexes of starches with GMS (1, 2 and 3%) disclosed faceted structures typical of crystals when observed by SEM and AFM, V-type crystalline pattern and endothermic peaks of dissociation between115 to 120 ° C, which classify them as IIb polymorphism. The results suggested that 1% of GMS was enough to complex with amylose and / or amylopectin molecules available for complexing in the wheat, normal corn, and waxy corn starches, whereas in the high amylose corn starch, concentrations below 3% GMS were not enough to saturate and complex all available amylose. The resistant starch ...